Choosing Death Over Survival: A Need to Identify Evolutionary Mechanisms Underlying Human Suicide - Chatterjee, Diya; Rai, Rishabh (Frontiers in Psychology, 2021)
The act of killing self contradicts the central purpose of human evolution, that is, survival and propagation of one’s genetic material. Yet, it continues to be one of the leading causes of human death. A handful of theories in the realm of evolutionary psychology have attempted to explain human suicide. The current article analyses the major components of certain prominent viewpoints, namely, Inclusive fitness, Bargaining model, Pain-Brain model, Psychological aposematism, and few other perspectives. The article argues that relatively more weightage has been given to understanding ultimate (the “why”) rather than proximate (the “how”) functionality of suicidal acts. Evolutionary theorists have consistently pointed out that to comprehensively understand a trait or behavior, one needs to delineate not only how it supports survival but also the evolution of the mechanisms underlying the trait or behavior. Existing theories on suicide have primarily focused on its fitness benefits on surviving kin instead of providing evolutionary explanations of the more complex mechanisms leading up to such self-destructive motivations. Thus, the current paper attempts to highlight this gap in theorizing while suggesting probable proximate explanations of suicide which stresses the need to diffuse attention paid to fitness consequences of the act alone. We speculate that such explorations are needed in order to build a robust and comprehensive evolutionary theory of human suicide.